Microwave assisted popping of five Andean cultivars of ñuña beans: Process optimization and effect of grain’s moisture content (Scientia Agropecuaria, 2024)
This research aimed to optimize the microwave popping process of 5 cultivars of ñuña beans under different moisture content. This work was divided into two stages: determining the optimal time and microwave power for maximum popping and studying the effect of initial grain moisture content on popping percentage. For this, grains were conditioned to 9%, 11%, 13% and 15% of moisture content. The results suggested that only the cultivars “Vaquita poroto”, “Negra” and “Jabona” cultivars reach the highest popping percentages selecting optimum microwave power and process time. In addition, this work found that for every studied cultivar, moisture content between 9 to 11% w.b (wet basis). is suitable to maximize popping percentage. Moisture contents greater than 13% w.b. drastically reduced the popping percentage but increased expansion percentage. In conclusion, this work recommended “Vaquita poroto” cultivar since it presented the maximum popping percentage even at moisture content up to 13% w.b. As practical applications, popping process using microwave has not been widely study, especially for non-conventional popping beans. These beans are consumed in South America; however, they can be exported as a healthy snack. In addition, this work optimized the process and selected the best cultivar of this bean to be industrialized. In addition, the present work demonstrated the importance of the initial moisture content of the beans to improve quality and yield of burst grains.
Keywords: ñuña bean; popping; microwave popping; legume grains; snack